Om ingen tar bort skräp är snart en stad förstörd: Kvindetid genbesøgt hos Julia Kristeva og Maja Ekelöf - Friis, Elisabeth (Passage - Tidsskrift for litteratur og kritik, 2025)
“If No One Removes the rubbish, a City is Quickly Destroyed: Women’s Time Revisited with Julia Kristeva and Maja Ekelöf” This article reads Swedish author Maja Ekelöf’s Report from a Floor Bucket (1971) in light of Julia Kristeva’s concept of Women’s time (1979). The form of Ekelöf’s diary from a life as a single mother with five children and night work as acleaning lady is characterised by the reproductive temporality in which she finds herself but also negotiates with otherforms of time listed by Kristeva: linear and monumental time.